LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF SILVER CATFISH (BAGRUS BAYAD FORSKAL, 1775) IN ZOBE RESERVOIR, DUTSINMA LOCAL GOVERNMENT AREA, KATSINA STATE, NIGERIA. - Dan-kishiya, Ahmed Salihu; Bichi, A. H.; Nababa, A. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Study on length-weight relationship and condition factor of Bagrus bayad from Zobe reservoir was conducted from April to July, 2017 to ascertain the growth pattern and the state of well-being of the species in the Reservoir. Specimens were obtained on weekly basis from the artisanal fishermen catches at their landing site in the Reservoir, for the period of the study. A total of 296 fish sample comprising of 145 males and 151 females were analysed. The result showed that the species exhibited negative allometric growth pattern with regression exponent b values of less than 3, while the correlation coefficient (r) values of 0.94 (males), 0.95 (each for females and combined sexes) revealed a strong positive correlation. The condition factor recorded is more than 1 which is an indication that the species is in good physiological state of well-being in the Reservoir